The perceived benefits of apps by construction professionals in New Zealand - Liu T; Mbachu J; Mathrani A; Jones B; McDonald B (MDPI AG)
The construction sector is a key driver of economic growth in New Zealand; however, its productivity is still considered to be low. Prior research has suggested that information and communication technology (ICT) can help enhance efficiency and productivity. However, there is little research on the use of mobile technologies by New Zealand construction workforce. This paper reports findings of an exploratory study with the objective of examining the perceived benefits regarding uptake of apps in New Zealand construction sector. Using self-administered questionnaire survey, feedback was received from the major construction trade and professional organisations in New Zealand. Survey data was analyzed using descriptive, one-sample t-test, Spearman’s rank correlation coefficient and structural equation modeling. Results showed that iPhone and Android phone currently dominate the smartphone market in New Zealand construction industry. The top three application areas are site photos, health and safety reporting and timekeeping. The benefits of mobile apps were widely confirmed by the construction professionals. The benefit of “better client relationship management and satisfaction” has substantial correlation with overall productivity improvement and best predictor of the overall productivity improvement. These findings provide a starting point for further research aimed at improving the uptake and full leveraging of mobile technologies to improve the dwindling productivity trend in New Zealand construction industry.
Keywords: construction industry; apps; mobile technology; productivity; smartphone; 1201 Architecture; 1202 Building; 1203 Design Practice and Management